99mTc-Labelled Compounds Prepared with Sodium Dithionite as Reducing Agent - Vilček, Š.; Kalinčák, M.; Macháň, V. (Nuklearmedizin - NuclearMedicine, 1981)
The paper deals with the application of Na2S2O4 as reducing agent in the preparation of 99mTc-labelled compounds. The reduction of pertechnetate can advantageously be carried out in neutral solutions of pH 7. Using this procedure, DTPA, HEDSPA, MDP, gluconate, citrate and trypsin were successfully labelled. In HEDSPA and MDP labelling, a high as cumulation of 99mTc in rat bones (50%) was obtained. In gluconate labelling, under various reaction temperatures, two types of complexes were prepared. Complex I shows a 99mTc biodistribution which is comparable with the kidney diagnosticum 99mTc-Sn-gluconate (24% of 99mTc in kidneys). Complex II, on the other hand, exhibited a reduced affinity of 99mTc to kidneys (2.2%) which, however, increases in bone to 15.4%. The experimental results indicated that Tc(V) is bound in Complex I. In technetium complexing no "mixed complex" is formed, technetium being complexed directly by chelate-forming groups of the labelled compound.